Insights into Classroom Dynamics: Indonesian EFL Teachers' Self-Efficacy in Instructional Strategies - Bachtiar, Bachtiar (Jurnal Basicedu, 2024)
Teachers' self-efficacy in instructional strategy has been indicated for its crucial role and function and its profound implications on teaching practices and student outcomes. This study aims to illuminate the intricate relationship between teachers' self-efficacy and their utilization of instructional strategies. Drawing upon Bandura's theory of self-efficacy, mixed-method research with convergent parallel design was employed to explore the perceptions and experiences of Indonesian EFL (English as a Foreign Language) teachers regarding their confidence in employing diverse instructional techniques within the classroom context. The data were collected through a questionnaire completed by 36 EFL teachers and semi-structured interviews involving six teachers. The results show that self-efficacy is pivotal in shaping instructional practices and highlight the need for targeted support and professional development initiatives to enhance teachers' confidence and competence in effectively employing varied instructional strategies. The results also show that learning facilities, time constraints, and curriculum change posed significant barriers to adopting certain strategies. This research contributes valuable insights to the field of EFL education, offering practical implications for teacher training programs and curriculum development efforts to optimize classroom dynamics and foster positive learning outcomes for students